Mudança climática e modal: dois caminhos que se cruzam - Ayroza, Mariana Rezende (2011)
Given the growing concern with the climate change issue and its consequences for society, we intend to analyse how the citizens pattern of travel impacts on fuel consumption in the municipalities. We use as a proxy for the trips, the fleet of municipal vehicles employing the model in panel of fixed effects. The result indicated that if there is a policy that encourages modal shift it will be possible to decrease the fuel consumption and hence the emission of greenhouse gases.